TATA KELOLA PEMERINTAHAN YANG TERABAIKAN DI PERBATASAN NEGARA: Disparitas Kebijakan Otonomi dan Erosi Loyalitas pada Batas Indonesia–Malaysia di Kalimantan Barat: Disparitas Kebijakan Otonomi dan Erosi Loyalitas pada Batas Indonesia–Malaysia di Kalimantan Barat - Ghina Raudatul Iryanti; silverius teyseran; Arzetika Amanda Putri; Muhammad Risqi; Christina Mega Putri Komar (Jurnal Ilmiah Administrasi Pemerintahan Daerah, 2025)
Border governance in Indonesia is regulated through a comprehensive normative framework, including Law No. 43/2008 on State Territory, Presidential Regulation No. 31/2015 on the Spatial Plan for Border Areas, and the 2025 Action Plan of the National Border Management Agency (BNPP). However, persistent inequalities remain in the Indonesia–Malaysia border region of West Kalimantan, where communities continue to face challenges related to accessibility, public services, information disparity, and socio-economic vulnerability. This article examines the discrepancy between regulatory mandates and field realities by employing a qualitative document-synthesis method that integrates legal documents, empirical reports, academic studies, and media coverage. The findings demonstrate a consistent pattern of multi-level governance failure, manifested in the inability of subnational governments to operationalize national border policies, limited fiscal and institutional capacity, and the absence of collaborative governance mechanisms. Consequently, communities in Entikong, Sajingan, Badau, and Jagoi Babang exhibit growing dependency on Malaysian services, leading to the erosion of national loyalty and state legitimacy. The article argues that the governance gaps in border management stem from structural weaknesses in coordination, asymmetric authority, and fragmented accountability across administrative layers. Strengthening border governance requires reconfiguring fiscal arrangements, enhancing intergovernmental coordination, and ensuring community-centered service delivery. Keywords: border governance, multi-level governance, social inequality, decentralization, West Kalimantan.